2015
DOI: 10.1039/c5ra11937e
|View full text |Cite
|
Sign up to set email alerts
|

Review: unraveling the less explored flocking technology for tissue engineering scaffolds

Abstract: Clinical translation of the scaffold-based tissue engineering (TE) therapy still faces multitude challenges despite intense investigations and advancement over the years. In order to circumvent clinical barriers, it is important to analyze the current technical challenges in constructing a clinically efficacious scaffold and subsequent issues relating to tissue repair. The major limitations of current scaffolds are lack of sufficient vascularisation, mechanical strength and issues related to the osseointegrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…To demonstrate how this flocking mechanism is fundamentally different than each of those previously reported (utilizing fiber finishes or inherently semiconductive materials), we flocked 0.5% AgNP/PCL fibers and surface-finished Rayon fibers after incubating at a different relative humidity (RH) for 24 h (Figure S2, Supporting Information). [1][2][3][4][5][6][7][8][16][17][18][19][20][21] Rayon fibers Theoretical cross-section view of PCL microfibers at different AgNP concentrations, (middle) photograph of microfibers with increasing (left to right) concentration of AgNPs, and (bottom) different concentration AgNP microfibers after cutting. b) Estimated conductivities using the Percolation Theory model for PCL microfibers loaded with 70 nm diameter AgNPs (conductivity threshold for flocking indicated with red arrow).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To demonstrate how this flocking mechanism is fundamentally different than each of those previously reported (utilizing fiber finishes or inherently semiconductive materials), we flocked 0.5% AgNP/PCL fibers and surface-finished Rayon fibers after incubating at a different relative humidity (RH) for 24 h (Figure S2, Supporting Information). [1][2][3][4][5][6][7][8][16][17][18][19][20][21] Rayon fibers Theoretical cross-section view of PCL microfibers at different AgNP concentrations, (middle) photograph of microfibers with increasing (left to right) concentration of AgNPs, and (bottom) different concentration AgNP microfibers after cutting. b) Estimated conductivities using the Percolation Theory model for PCL microfibers loaded with 70 nm diameter AgNPs (conductivity threshold for flocking indicated with red arrow).…”
Section: Resultsmentioning
confidence: 99%
“…Electrostatic flocking, a textile engineering technique that consists of three main components (flock fibers, an adhesive, and a substrate) uses an electrostatic field to launch short microfibers (flock fibers) toward an adhesive-covered substrate, creating a layer of vertically-aligned fibers perpendicular to the substrate. [1,2] Generally, flocking can be regarded as a surface modification technique used to decorate object surfaces or planar textiles. Application of flock fibers (short polymeric microfibers with proprietary electrostatic surface finishes) to an object increases regional mechanical strength, generates anisotropic surfaces with high surface areas and porosities, and allows for surface functionalization based on the type of fiber used.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Moreover, electrostatic flocking technology has been used for the preparation of three-dimensional anisotropic scaffolds, featuring a columnar fiber orientation to enhance the biomechanical properties under compression. [19][20][21][22][23] Gossla and colleagues recently prepared flocked scaffolds consisting of chitosan only, ensuring full biodegradability. 24 It was found that these scaffolds were suitable for the proliferation of hMSC and Saos-2 cell lines, hence they were proposed as a promising candidate for articular cartilage TE applications.…”
mentioning
confidence: 99%
“…These composites can potentially provide improved, reversible adhesion compared to traditional bio‐polymers 18,19 . Originally envisioned as adhesive tapes or as stability mechanisms in robotic climbers, they can also function as scaffolds in tissue engineering 20 …”
Section: Introductionmentioning
confidence: 99%
“…18,19 Originally envisioned as adhesive tapes or as stability mechanisms in robotic climbers, they can also function as scaffolds in tissue engineering. 20 The design of a base layer for tissue sealants requires materials capable of conforming to the gross anatomy that control fluid permeability while maintaining biocompatibility. Electrospinning is the preferred technique for creating fibrous mats in controlled, designed architectures.…”
Section: Introductionmentioning
confidence: 99%